High-throughput screening the micro-mechanical properties of polyimide matrix composites at elevated temperatures. (March 2022) - Shen, Sijia; Li, Hongbo; Yang, Lingwei; Li, Na; Wu, Jinting; Zhao, Tingxing
Abstract: In this work, a novel high-throughput methodology based on combinations of nanoindentation, indentation creep and push-in methods, is proposed to measure in-situ the micro-mechanical properties of typical polymer matrix composites at a wide temperature range. The Young's modulus and strain rate sensitivity of a polyimide matrix and the interfacial shear strength in a quartz fiber reinforced polyimide matrix composite are measured at 25–350 °C for the first time. The results highlight a linear softening of the polyimide matrix at high temperatures, which is evidenced by the approximate linear decrease of Young's modulus from ≈5.0 GPa at 25 °C to ≈1.1 GPa at 350 °C. In comparison, the strain rate sensitivity of the polyimide matrix is increased, from ≈0.032 at 25 °C to ≈0.062 at 350 °C. This evidences a stronger visco-plasticity of polyimide at higher temperatures. The shear strength of the fiber/matrix interface is also temperature dependent. As the testing temperature increases from 25 to 300 °C, the shear strength is decreased from ≈147 MPa to ≈40 MPa. Specially, the interfacial strength is extremely low at 350 °C (≈4 MPa), evidencing a failure of the composite at this temperature. Highlights: A novel methodology was proposed to measure the micro-mechanical properties of polymer matrix composite at high temperatures. Significant mechanical degradations in polyimide and interfaces occurred at high temperatures based on the methodology. The strain rate sensitivity of polyimide matrix was quantified at 25 350 ℃, based on an indentation creep technique.